Hibernation in a primate: does sleep occur?. Issue 8 (August 2016) - Blanco, Marina B.; Dausmann, Kathrin H.; Faherty, Sheena L.; Klopfer, Peter; Krystal, Andrew D.; Schopler, Robert; Yoder, Anne D.
Abstract : During hibernation, critical physiological processes are downregulated and thermogenically induced arousals are presumably needed periodically to fulfil those physiological demands. Among the processes incompatible with a hypome tabolic state is sleep. However, one hibernating primate, the dwarf lemur Cheirogaleus medius, experiences rapid eye movement (REM)-like states during hibernation, whenever passively reaching temperatures above 30°C, as occurs when it hibernates in poorly insulated tree hollows under tropical conditions. Here, we report electroencephalographic (EEG) recordings, temperature data and metabolic rates from two related species ( C. crossleyi and C. sibreei ), inhabiting high-altitude rainforests and hibernating underground, conditions that mirror, to some extent, those experienced by temperate hibernators. We compared the physiology of hibernation and spontaneous arousals in these animals to C. medius, as well as the much more distantly related non-primate hibernators, such as Arctic, golden-mantled and European ground squirrels. We observed a number of commonalities with non-primate temperate hibernators including: (i) monotonous ultra-low voltage EEG during torpor bouts in these relatively cold-weather hibernators, (ii) the absence of sleep during torpor bouts, (iii) the occurrence of spontaneous arousals out of torpor, during which sleep regularly occurred, (iv) relatively high early EEG non-REM during the arousal, and (v) a gradual transition to the torpid EEG state from non-REM sleep. Unlike C. medius, our study species did not display sleep-like states during torpor bouts, but instead exclusively exhibited them during arousals. During these short euthermic periods, non-REM as well as REM sleep-like stages were observed. Differences observed between these two species and their close relative, C. medius, for which data have been published, presumably reflect differences in hibernaculum temperature.